Intellectual Property Law Counseling for Micro, Small and Medium Enterprises - M. Citra Ramadhan; Montayana Meher; Sri Hidayani; Agung Suharyanto (Universitas Medan Area, 2026)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in strengthening the national economy, especially in encouraging real sector growth and community income distribution. However, the use of the Intellectual Property (IP) system as a form of legal protection for MSME products is still minimal. The low understanding of business actors regarding the importance of IP registration, as well as cost constraints and access to information, are the main obstacles. This Community Service (PKM) activity was conducted at the Ar-Rahman Mosque, Hamlet X, Medan Krio Village, Sunggal District, Deli Serdang Regency, to increase public awareness and understanding of the application of IP in MSME products. The implementation method is carried out through lectures and Focus Group Discussions (FGD), which discuss the types of IP, the importance of copyright registration, trademarks, simple patents, and industrial design. The results of the activity showed an increase in participants' understanding of the urgency of legality and legal protection for their business products, as well as the encouragement to legalize and officially register businesses immediately. This activity is expected to be able to strengthen the position of MSMEs in the face of increasingly competitive market competition